Eye movement desensitization and reprocessing versus cognitive behavioral therapy : Which works better for post-traumatic stress disorder in Pakistan? A two-year longitudinal study - Anwar, Khan; Amalia, Madihie (2023)
Background and Aim: Post-Traumatic Stress Disorder (PTSD) is a psychiatric disorder, triggered by traumatic events. Modern evidence-based psychotherapies, like, Eye Movement Desensitization & Reprocessing (EMDR) and Cognitive Behavioral Therapy (CBT) have been used for the treatment of PTSD, however, little evidence exists regarding the comparative efficacy of these two psychotherapies, especially in Pakistan. Keeping this research gap in view, the current Randomized Controlled Pilot Study has determined the comparative efficacy of EMDR and CBT in Pakistan.